Bis-subporphyrin-like boron(iii) complexes derived from indolo[2,3-a]carbazole-based cyclic bis-BODIPYs exhibiting persistent helical chirality - Spergen, Aswini; Bal, Pranav V.; Shameem, Asif Khan Shameer; Joshy, Arun; Nambiar, Anjana P.; Andrews, Alex P.; Sabapathi, Gokulnath (Chemical Science, 2025)
Herein, we report the synthesis of 11,12-dihydroindolo[2,3-a]carbazole (InC) 1 incorporating expanded porphyrinoid 8, and its boron(iii) complexes (8BF2 and 8BF). These macrocycles exhibit a `figure-eight' conformation that exists as a pair of helical enantiomers (P,P and M,M), confirmed by X-ray crystallographic analysis. The `figure-eight' structures are stabilized by intramolecular hydrogen bonds such as NH & ctdot;N and NH & ctdot;F interactions. The synthesized macrocycles demonstrate excellent stability under ambient conditions. Further, the helically-locked structure 8BF exhibited closely held InC units with a distance of 6.17 & Aring; and enabled facile optical resolution using chiral HPLC. Circular dichroism spectroscopy of enantiopure 8BF shows the Cotton effect at 692 nm extending to the near-IR region with Delta epsilon up to 150 M-1 cm-1. The chiral induction of racemic macrocycle 8 was employed using enantiopure mandelic acids.